Development of home education-based worksheets at SD Muhammadiyah Sirojuddin - Aditia Eska Wardana; Dian Mutiara Sakti; Hesti Nurrohmah; Indri Nursiyah; Irma Antonia Aisyah; Saman Hudi Almustaqim (Universitas Muhammadiyah Magelang, 2022)
Due to the current state of education, which is hampered by the Covid-19 virus, the learning process is conducted entirely online. SD Muhammadiyah Sirojuddin is having trouble implementing online learning and does not yet have materials for at-home learning. The PPMT team has devised a solution to these issues by providing training in the creation of home-based modules. The objective of the project is to introduce teachers to home-based learning modules, provide assistance in creating modules, and provide assistance to teachers who are having difficulty preparing modules. Training and assistance in the preparation of home-based modules/worksheets are provided as part of the service method. This activity resulted in a Natural Sciences (IPA) subject module for grade 4 that included material on the Application of Light Properties that students could study at home.